Pour une méthode diaristique en anthropologie - Pierre Depardieu (Ateliers d'Anthropologie)
By analysing excerpts from a given diary, the article aims to show the methodological and epistemological potential of a diaristic approach in social sciences, especially in anthropology. After having established a basic opposition between diary and narrative, as well as a few methodological elements, one can observe several first-level phenomena in the material (namely ellipses, the interweaving of narrative threads, focus effects, the frailty of reported speech, the constant contextualization of facts, as well as the absence of closure mechanisms) that could inspire considerations on the status of diaries in anthropology and the possible benefits that could be expected from their use. The purpose is to test a way of using a diary in a heuristic process, so that the first features of what could become “diaristic anthropology” can emerge.